A Novel Intelligent Optimization Algorithm Inspired from Circular Water Waves - Colak, Muhammed Emre; Varol, Asaf (Kaunas Univ Technology, 2015)
In this paper, a novel nature inspired algorithm for continuous optimization of numerical functions has been proposed. The algorithm is inspired from the circular wave created from a water drop when it falls to a still water. Algorithm itself has been developed with the purpose of distributed working thus kept as embarrassingly parallel as possible. Proposed algorithm is tested with eight different benchmark functions and up to thirty dimensions. The experimental results are promising and encouraging for further research studies.
Keywords: Optimization; nature-inspired computing; iterative methods; performance